2013
DOI: 10.1038/nature12501
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin maintains high endothelial venule integrity by interacting with platelet CLEC-2

Abstract: Circulating lymphocytes continuously enter lymph nodes (LNs) for immune surveillance through specialised blood vessels named high endothelial venules (HEVs)1–5, a process that increases dramatically during immune responses. How HEVs permit lymphocyte transmigration while maintaining vascular integrity is unknown. Here, we report a role for the transmembrane O-glycoprotein podoplanin (PDPN, also known as gp38 and T1α)6–8 in maintaining HEV barrier function. Mice with postnatal deletion of PDPN lost HEV integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
277
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(285 citation statements)
references
References 37 publications
6
277
2
Order By: Relevance
“…31 Herzog et al demonstrated that platelets CLEC-2 is necessary to maintain HEV stability postlymphocyte migration. 25 In this manuscript, the author did not report on the impact of the loss of CLEC-2 on the immune response. Here we expand these observations and explore their functional relevance demonstrating that, while loss of CLEC-2 has no direct immunological consequences in the immune responses upon single immunization, LN status after chronic antigenic stimulation is largely impaired when CLEC-2 expression on platelets is missing.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…31 Herzog et al demonstrated that platelets CLEC-2 is necessary to maintain HEV stability postlymphocyte migration. 25 In this manuscript, the author did not report on the impact of the loss of CLEC-2 on the immune response. Here we expand these observations and explore their functional relevance demonstrating that, while loss of CLEC-2 has no direct immunological consequences in the immune responses upon single immunization, LN status after chronic antigenic stimulation is largely impaired when CLEC-2 expression on platelets is missing.…”
Section: Discussionmentioning
confidence: 97%
“…Clec1b-deficient DCs have been shown to fail to access the Gp38 1 afferent lymphatics, reducing T-cell priming and antigen response in LNs, 24 while a role for CLEC-2 in HEV maintenance was reported during the revision of this manuscript. 25 In our study, we took advantage of the Clec1b PF4-Cre conditional mouse, in which Clec1b expression is selectively deleted on the megakaryocyte/platelet lineage, to dissect the role of CLEC-2 in the development of the LN anlage in the embryo and the maintenance of the LN structure and function in adult life.…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the blood vasculature of all studied organs in CD73-deficient mice has been shown to be leakier to small molecules in multiple models of ischemiareperfusion injury and LPS-induced inflammation when compared to WT mice. Since CD73 is inducible in ischemic and inflammatory stimuli [31,32], and since the steady-state permeability in different vascular beds varies substantially [33], it was relevant to address the role of CD73 in permeability control within the lymphatic system under normal conditions. Our data with the cultured human ECs, and more notably, the in vivo experiments with the CD73-deficient mice clearly showed that CD73 is involved in the control of basal vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Also, CLEC-2-positive dendritic cells interact with Pdpn-positive LEC and follicular reticular cells for their migration from the periphery to and through the lymph node where they present antigens to T-cells (18). Very recently, the interaction between CLEC-2-positive plate-lets and Pdpn-positive follicular reticular cells was reported to be involved in maintaining the integrity of high endothelial venules (19).…”
mentioning
confidence: 99%